Evaluation of furrow and tape irrigation methods in sugarbeet fields - H.R. Salemi (Sugar Beet Seed Institute, 2014)
Due to water scarcity, sustainable development of drip irrigation tape is essential in Iran. A number of drip irrigation tape systems used in sugar beet fields in Isfahan and Chaharmahal and Bakhtiari provinces were evaluated and were compared with furrow irrigation method for two years. Actual water use efficiency in lower quarter, water use efficiency potential, dropper uniformity in lower quarter, absolute water output uniformity of droppers, Christiansen’s uniformity coefficient, uniformity of water distribution as well as the quantity and quality of sugar beet were investigated in this study. Orion and Afshari cultivars were planted on 0.4 m rows. Actual water use efficiency varied in the range of 49-74.5%. Average uniformity of distribution coefficient of the droppers was 73.8% and Christiansen’s uniformity coefficient was 82%. Drip irrigation tape system had significant difference with furrow irrigation method in terms of water use efficiency for sugar yield and white sugar content (p  0.05). Average water use efficiency for sugar yield and white sugar content in drip irrigation tape were 0.91 and 0.65 Kg m-3, respectively, and for furrow irrigation system were 0.78 and 0.53 Kg. m-3, respectively. Both irrigation systems had no significant difference in terms of root yield and sugar beet quality.